Agronomic and technological characteristics of the common bean cultivars grains of the black commercial group in the winter season (Revista de Ciências Agroveterinárias, 2012)
Beans are one of the foods more produced in all nationwide, with intense search for productive cultivars, adapted to local cultivation and with good culinary characteristics. The aim of this work was to evaluate the cultivars performance of the black commercial group bean, with regard to agronomic and technological characteristics in the winter season in Jaboticabal, SP. The experiment was conducted in a split plot design with three replications, and the used of the cultivars: IAC Una, Diamante Negro, Ônix, BRS Campeiro, BRS Grafite, BRS Supremo, BRS Valente, IPR Graúna, IPR 88 Uirapuru and FT Nobre. Among the yielding components, there were significant differences just the mass per 100 grains. Stood out in the yield the BRS Campeiro, Diamante Negro and IAC Una with values of 3,971, 3,755 and 3,667 kg ha-1, respectively. The IPR Graúna showed lowest cooking time, 20 minutes, positioning themselves as medium susceptibility cooking time. The cultivars showed satisfactory performance in the relation of hydration, obtaining values above 2.0 and a maximum grains hydration time, ranging between 9 hours 15 minutes and 10 hours 58 minutes.
Keywords: Phaseolus vulgaris; Varieties; Yield; Cooking time; Grains hydration.